2020
DOI: 10.1097/jxx.0000000000000415
|View full text |Cite
|
Sign up to set email alerts
|

Driving high-functioning clinical teams: An advanced practice registered nurse and physician assistant optimization initiative

Abstract: Background: Rapid changes in the health care marketplace are driving health care systems to modify operations by which the advanced practice registered nurse (APRN) and physician assistant (PA) clinicians serve patients. By identifying more effective and efficient utilization workflows, organizations can meet these demands resulting in high-functioning clinical teams. Local problem: With the growing number of APRNs and PAs within a large academic medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…Other care team members included nurses, pharmacists, clinical/medical assistants, integrated behavioural health staff and social workers. A primary principle of the care team design was for all members to be working to the fullest extent of their licensure and training, which has been shown to improve the efficiency of care within the care team 19,20 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other care team members included nurses, pharmacists, clinical/medical assistants, integrated behavioural health staff and social workers. A primary principle of the care team design was for all members to be working to the fullest extent of their licensure and training, which has been shown to improve the efficiency of care within the care team 19,20 …”
Section: Methodsmentioning
confidence: 99%
“…A primary principle of the care team design was for all members to be working to the fullest extent of their licensure and training, which has been shown to improve the efficiency of care within the care team. 19,20 The cost of care was measured with the cost per member per month (PMPM) metric. Every clinician in this study had a panel of patients, and each patient in the panel had a sum of total charges of all services provided for 12 months.…”
Section: Settingmentioning
confidence: 99%
“…1, 2 Brooks and Fulton evaluated APRN and physician assistant (PA) practice in an assessment of more than 200 practitioners and concluded that APRNs and PAs are in a unique position to assist with addressing many current challenges in healthcare. 4 The use of collaborative practice models and allowing APRNs to practice to the full extent of their license, training, and education will result in optimal patient outcomes and effectiveness. 4 Another model presented by Waldrop and colleagues supported advanced practice providers including NPs, PAs, and CRNAs, but didn't include CNSs or CNMs in the model for practice.…”
mentioning
confidence: 99%
“…4 The use of collaborative practice models and allowing APRNs to practice to the full extent of their license, training, and education will result in optimal patient outcomes and effectiveness. 4 Another model presented by Waldrop and colleagues supported advanced practice providers including NPs, PAs, and CRNAs, but didn't include CNSs or CNMs in the model for practice. 5 APRNs are recognized as key players to drive a more efficient workforce through their capacity to negotiate issues of health and social well-being in a variety of settings, both institutional and community as well as acute and chronic care.…”
mentioning
confidence: 99%
“…Advanced practice providers who practice at the top of their license, education, and scope positively impact healthcare delivery to patients. Numerous studies demonstrate that APP care in the acute care setting has outcomes equivalent to that of physicians [1][2][3][4][5][6] and are associated with decreased complications, length of stay (LOS), and cost of care. 3,7 Advanced practice providers are available to other members of the healthcare team to discuss and provide direction for patient care, and contribute to improvements in continuity of care, access, patient safety/quality, physician productivity, nursing engagement, and patient throughput.…”
mentioning
confidence: 99%